2018
DOI: 10.1021/jacs.7b11955
|View full text |Cite
|
Sign up to set email alerts
|

Ce3+-Doping to Modulate Photoluminescence Kinetics for Efficient CsPbBr3 Nanocrystals Based Light-Emitting Diodes

Abstract: Inorganic perovskite CsPbBr nanocrystals (NCs) are emerging, highly attractive light emitters with high color purity and good thermal stability for light-emitting diodes (LEDs). Their high photo/electroluminescence efficiencies are very important for fabricating efficient LEDs. Here, we propose a novel strategy to enhance the photo/electroluminescence efficiency of CsPbBr NCs through doping of heterovalent Ce ions via a facile hot-injection method. The Ce cation was chosen as the dopant for CsPbBr NCs by virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
385
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 480 publications
(399 citation statements)
references
References 41 publications
9
385
1
4
Order By: Relevance
“…According to the Burstein–Moss effect in heavily doped n-type semiconductors, slight blue shifts of both absorption and PL positions can be attributed to the filling of the state by the donated electrons of Yb 3+ around the bottom of the conduction band, which leads to some band gap widening. 41 Their powder XRD patterns confirmed that their crystal structure still adopts the tetragonal phase (JCPDS No. PDF#18–0366) with the space group P4mm (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…According to the Burstein–Moss effect in heavily doped n-type semiconductors, slight blue shifts of both absorption and PL positions can be attributed to the filling of the state by the donated electrons of Yb 3+ around the bottom of the conduction band, which leads to some band gap widening. 41 Their powder XRD patterns confirmed that their crystal structure still adopts the tetragonal phase (JCPDS No. PDF#18–0366) with the space group P4mm (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…As typical defect‐tolerant materials, doping is an effective strategy to produce perovskites with high PL efficiencies and stability, and suitable electrical properties . Hence, the stability and PLQY are obviously enhanced by reducing the defect state density and passivating grain boundaries, leading to excellent optoelectronic properties for devices constructed by using the doped perovskites as active layers . Typically, various metal ions, including Bi 3+ , Ni 2+ , Mn 2+ , Cu 2+ , Zn 2+ , Cd 2+ and rare earth ions (eg, Ce 3+ , Er 3+ , Yb 3+ ), have been doped into halide perovskites.…”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 99%
“…63 Copyright 2018 American Chemical Society optoelectronic properties for devices constructed by using the doped perovskites as active layers. [78][79][80][81][82] Typically, various metal ions, including Bi 3+ , Ni 2+ , Mn 2+ , Cu 2+ , Zn 2+ , Cd 2+46,48,50,83-85 and rare earth ions (eg, Ce 3+ , Er 3+ , Yb 3+ ), 86 have been doped into halide perovskites. In the halide perovskite system, the similar bond energy between doped elements with X and Pb-X is considered to be one of the key factors that favors impurity incorporation.…”
Section: B-site Doping/substitution For Blue-emissive Perovskitesmentioning
confidence: 99%
“…1115 Several studies also reported improvements of EQEs of CsPbBr 3 NC-based LEDs utilizing the suitable metal ion doping: namely from 0.8% to 1.4% via Mn 2+ doping; 16 from 1.0% to 4.1% via Sn 4+ doping; 17 and from 1.6% to 4.4% via Ce 3+ doping. 18 …”
mentioning
confidence: 99%